Rights, gender and family law - Wallbank, Julie A.; Choudhry, Shazia; Herring, Jonathan (Routledge, 2009)
There has been a widespread resurgence of rights talk in social and legal discourses pertaining to the regulation of family life, as well as an increase in the use of rights in family law cases, in the United Kingdom, the United States, Canada and Australia. This title addresses the implications of these developments.